On empathy: Fundamental issues regarding its nature and teaching - H. Brink (AOSIS, 1991)
In nursing empathy is generally regarded as an essential component of nurse-patient interaction, but there appears to be a lack of clarity among nurse educators and professional nurses regarding its nature and how it may be taught and measured. This paper focuses on an analysis of selected theoretical works related to the nature and teaching of empathy, and an attempt is made to identify fundamental issues regarding the phenomenon "empathy" and its place in clinical nursing practice.